Hyaluronidase injection for anal hematoma in a high-risk patient: a case report - Pansare, Snehal G.; Wavhal, Payal P. (International Surgery Journal, 2026)
Anal hematomas are benign anorectal lesions that often resemble thrombosed haemorrhoids. Conventional management ranges from conservative therapy to excision. In elderly patients with major comorbidities, surgical intervention may be unsafe. This report describes the first known documented use of intralesional hyaluronidase to treat a large anal hematoma in a high-risk patient. A 70-year-old woman with hypertension, ischemic heart disease, and hypothyroidism (ejection fraction 55%) presented with a 4-cm bluish swelling at the 7 o’clock perianal position, initially mistaken for a prolapsed haemorrhoid. She was deemed unfit for anaesthesia. After counselling and informed consent, intralesional hyaluronidase was injected directly into the lesion. The swelling regressed rapidly, symptoms resolved, and bowel function normalized with supportive medication. No complications or recurrence were observed during three months of follow-up. Hyaluronidase breaks down hyaluronic acid in the extracellular matrix, reducing tissue turgor and promoting resorption. It is well established in dermatology and ophthalmology but has not been reported in anorectal conditions. This case suggests it may provide a minimally invasive alternative in carefully selected patients for whom conventional surgery is contraindicated. Limitations include the single-case nature of the report and lack of standardized dosing. Intralesional hyaluronidase may be a safe and effective treatment for large anal hematomas in high-risk surgical patients. Further clinical studies are warranted.